A Bispidine Based CuII/ZnII Heterobimetallic Coordination Polymer. Issue 21 (3rd May 2022) - Lippi, Martina; Wadepohl, Hubert; Comba, Peter; Cametti, Massimo
Abstract: The metalloligand approach was used to obtain a novel Cu II /Zn II heterobimetallic coordination polymer (CP) 1, based on the carefully designed bispidine ligand L4 . CP 1, characterized by single crystal (SC‐) and powder X‐ray diffraction methods (P‐XRD), is constituted by repeating large 32‐membered macrocycles forming ribbon‐like linear arrays and it features a Cu II ‐coordination site occupied by a markedly labile MeCN. We also describe the synthesis and characterization of intermediate metalloligands (with Cu II, Fe III, Mn II, and Pd II, the latter three obtained as SCs and characterized accordingly) and provide a view of potential intermediate species along the route from metalloligands to heterometallic CPs. Abstract : The metalloligand approach has been employed to obtain a Cu II /Zn II heterometallic coordination polymer based on a newly designed bispidine ligand with both convergent and divergent metal binding sites.